2011
DOI: 10.1093/bja/aer033
|View full text |Cite
|
Sign up to set email alerts
|

ICU fire evacuation preparedness in London: a cross-sectional study

Abstract: Forward planning for an urgent evacuation can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
(1 reference statement)
0
32
0
Order By: Relevance
“…19 More than 50% of hospital evacuations are due to internal hospital events, but the most severe problems and largest scale hospital evacuations have been due to natural hazards. 19 Hospitals are poorly prepared to deal with these events, 20 and there are signifi cant operational challenges to moving patients from hospital areas to the ground fl oor for evacuation 21 or to makeshift landing zones on rooft ops and in parking garages. 13 , 22 , 23 Simulated vertical evacuations provide excellent examples of the challenges and technical considerations involved with this task 21 , 24 -26 (see e-Appendix 2 for an example 27 ) Th erefore, disaster plans that consider staffi ng requirements for safe and rapid vertical evacuation are important.…”
Section: C We Suggest Hospital Exercises Should Simulate a Mass Crimentioning
confidence: 99%
“…19 More than 50% of hospital evacuations are due to internal hospital events, but the most severe problems and largest scale hospital evacuations have been due to natural hazards. 19 Hospitals are poorly prepared to deal with these events, 20 and there are signifi cant operational challenges to moving patients from hospital areas to the ground fl oor for evacuation 21 or to makeshift landing zones on rooft ops and in parking garages. 13 , 22 , 23 Simulated vertical evacuations provide excellent examples of the challenges and technical considerations involved with this task 21 , 24 -26 (see e-Appendix 2 for an example 27 ) Th erefore, disaster plans that consider staffi ng requirements for safe and rapid vertical evacuation are important.…”
Section: C We Suggest Hospital Exercises Should Simulate a Mass Crimentioning
confidence: 99%
“…During Joint Commission hospital surveys in the United States, a frequently cited issue related to fire and life safety standards is noncompliance with maintaining the integrity of exits (“Compliance Rates,” ; McLaughlin, ). In the United Kingdom, Murphy and Foot () surveyed ICU fire evacuation preparedness at 35 adult and pediatric ICUs within London in 2008, and found that fire evacuation preparedness was compromised by inadequate escape routes (62% had only one or two escape routes), a lack of portable monitoring equipment and emergency drug supplies, and no evacuation plan rehearsals. Only 14 ICUs had a formal triage policy for patient evacuation, which was based on the proximity to the fire and illness severity (Murphy & Foot, ).…”
Section: Challenges To Maintain the Integrity Of Exitmentioning
confidence: 99%
“…In the United Kingdom, Murphy and Foot () surveyed ICU fire evacuation preparedness at 35 adult and pediatric ICUs within London in 2008, and found that fire evacuation preparedness was compromised by inadequate escape routes (62% had only one or two escape routes), a lack of portable monitoring equipment and emergency drug supplies, and no evacuation plan rehearsals. Only 14 ICUs had a formal triage policy for patient evacuation, which was based on the proximity to the fire and illness severity (Murphy & Foot, ). Additional statistics follow (Murphy & Foot, ): these 35 ICUs were located in the basement and as high as the eleventh floor 34 ICUs (97%) expected to evacuate using the stairs, and only seven (20%) of them had step‐free ground floor access (e.g., ramps) 11 of the 28 ICUs located above the ground floor had an under‐mattress evacuation sheet (e.g., ski sheets) or alternative evacuation aids only one of the 28 ICUs located above the ground floor had an evacuation plan to transport patients downstairs …”
Section: Challenges To Maintain the Integrity Of Exitmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it recommended further training and protocol use in the care of ICU patients with tracheostomies. 1 Our current practice for training staff in tracheostomy emergencies includes high fidelity simulation, both in-situ and within a simulation centre. Challenges to this, however, include high resource requirements and limited reach to staff.…”
mentioning
confidence: 99%